Endobronchial tuberculosis simulating a tumor: an interesting case report - Ganesan, Natesh; G., Prasanth; Vadivelu, Gangadharan (International Journal of Advances in Medicine, 2022)
Endobronchial tuberculosis (EBTB) is a special form of TB which is associated with significant morbidity and potential mortality. EBTB is the infection of tracheobronchial tree, and continues to remain challenging for clinicians to diagnose. The incidence of EBTB has been reported to be 5.8% to 30% in people with pulmonary TB. 60-year-old male, chronic smoker presented with complaints of dyspnea, cough with expectoration and sore throat for 2 weeks. General examination showed patient to have pallor and respiratory system examination showed decreased breath sounds in left infraaxillary region and bilateral crepitations. Routine blood investigations done showed decreased hemoglobin levels, elevated total leukocyte count, ESR. Sputum AFB was negative. Mantoux-15 mm in duration. Chest X-ray showed homogenous opacities over the left lower zone and elevated right diaphragm. CT thorax done showed a subsegmental peripheral soft tissue density 4.3×2.2 cm in the inferior lingula segment. Bronchoscopy showed whitish plaques over the anterior tracheal wall near carina and over left main bronchus. Endobronchial tissue growth seen occluding the lingula bronchus. Biopsy was taken and histopathology showed a granulomatous lesion, BAL Gene Xpert was positive for MTB. Patient was started on 3 tablets ATT. Clinicians need to be vigilant in patients who are AFB smear negative, with symptoms; bronchoscopy should be considered in those selected cases.